Perceived social support and the experience of intimate partner violence among married and cohabiting young women in urban slums, Ibadan, Nigeria: a descriptive study - Olufunmilayo I Fawole; Omowumi O Okedare (BMJ Public Health)
Background Social support is an important factor for improving the outcome of intimate partner violence (IPV) among abused women. Gaps exist on the role of social support among young women who have experienced IPV in Nigeria. Therefore, this study examined the influence of social support on the experience of IPV married and cohabiting young women in urban slums of Ibadan, Nigeria.Methods This study was a community-based household survey conducted in ten slum communities in the five local government areas of Ibadan municipality among 314 young women. Outcome variable was the experience of physical, psychological and any IPV. Socio-demographic characteristics were summarised using frequency and percentage. Level of statistical significance was set at α0.05.Results The mean age of respondents was 22.25±1.75 years and the mean spousal age difference was 7.15±3.87 years. Majority of the respondents were married (62.1%), and have been in a union for 0–4 years (68.8%). More than half (56.4%) justified IPV perpetration. Majority of the respondents reported having experienced psychological IPV (66.6%) and at least one form of IPV (86.3%) but have never told anyone about their IPV experience (58.1%). Social support was a predictor of psychological and any IPV, but not physical IPV. Type of union and duration of union significantly predicted all forms of IPV.Conclusion Prevalence of IPV is higher among women in cohabiting relationships. Social support from family and friends helps abused women cope with the experience of IPV. Thus, IPV prevention should target the social support system available to abused women.